Vaginal hysterectomy versus vaginal assisted NOTES hysterectomy (VANH): a protocol for a randomised controlled trial - Merel Kimman; Ilse Bekkers; Lynn Hoen; Huib A A M van Vliet; Nicol A C Smeets; Anne Damoiseaux; Martine M L H Wassen (BMJ Open)
Introduction Natural Orifice Transluminal Endoscopic Surgery is a minimal invasive technique using natural body orifices like the vagina. Benefits of a vaginal assisted NOTES hysterectomy (VANH) are no visible scars, less blood loss, shorter surgery time and it allows more women to undergo a hysterectomy in a day-care setting compared with the total laparoscopic hysterectomy. Trials comparing vaginal hysterectomy (VH) and VANH are lacking. The aim of this study is to compare hysterectomy by VANH versus VH for same-day discharge (SDD), complications, surgical outcomes, postoperative recovery, quality of life, costs and cost-effectiveness.Methods and analysis The study is a single-blinded, multicentre, randomised controlled trial. Eligible women with benign indication for hysterectomy will be randomly allocated to the VH (control) group or the VANH (intervention) group. The primary outcome is SDD. We calculated a sample size of 124 women assuming 27% SDD difference with an alpha of 0.05 and power of 0.8. A total of 83 patients will be included in the VANH-group and 41 patients in the VH-group, using an enrolment ratio of 2:1. Secondary outcomes are; surgery-related complications, surgical outcomes, postoperative recovery, quality of life, costs and cost-effectiveness.Ethics and dissemination The study was approved on 27 May 2021 by the Ethics Committee of the Zuyderland Medical Centre Heerlen. The first patient was randomised on 8 July 2021. The last participant randomised should be treated before 31 December 2022. The results will be presented in peer-reviewed journals and at scientific meetings within 4 years after starting recruitment.Trial registration number NCT04886791.